Development of an Evaluation Tool for Academic Coordination Performance in Public Secondary Schools - Cordero Redondo, Joan Javier (2025)
Educational institutions evaluate the performance of academic departments, an essential activity for identifying opportunities for improvement, change, and replication. However, the role of Academic Coordination (AC) lacks a dedicated tool for performance assessment. This study aims to develop an instrument for validating and evaluating AC in secondary schools. The research employed a mixed-methods approach with a descriptive design based on a case study. For validation, in-depth interviews (4 persons) and surveys (30 participants) were conducted, these tools were designed based on a review of current specialized literature and consultations with expert professionals. The construction of the instrument was informed by an analysis of participant consultations and expert input. The AC evaluation instrument consists of four areas with numerical indicators that quantitatively assess performance: (1) Planning and instructional design; (2) Administrative support and curricular activities; (3) Support for improving the teaching-learning process; and (4) Monitoring and communication tasks. These areas are interconnected and reflect the core responsibilities identified during the research. A key shortcoming in the historical development of the AC role has been the absence of pedagogical and scientific substance through education and training. The developed instrument can assess AC performance across the 740 public secondary schools nationwide, addressing existing gaps. Its use and scope should be communicated through reports to educational circuits and regional offices at the end of 3- or 6-month cycles.